Experimental precision of wheat trials in homogeneous adaptation regions - Benin, Giovani; Storck, Lindolfo; Marchioro, Volmir Sérgio; Franco, Francisco de Assis; Schuster, Ivan (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the adequacy of measures of the experimental precision degree in trial sets of genotype competition in wheat (Triticum aestivum), carried out in homogeneous adaptation regions. The statistics heritability, coefficient of determination, F‑test value for genotype, Fasoulas differentiation index, selective accuracy, and repeatability coefficient were calculated from results of wheat grain yield obtained in 572 competition trials with 25 genotypes, in four homogeneous adaptation regions in the crop years from 2007 to 2011. Linear correlations among the statistics were estimated and path analysis was performed. Statistics were grouped using Ward’s hierarchical method. Statistical means from each adaptation region were compared by the t bootstrap test. The statistics selective accuracy, coefficient of determination, coefficient of heritability, and repeatability coefficient are algebraically related and are suitable to evaluate the experimental accuracy of wheat competition trials in different adaptation regions. The regions used for the evaluation of values for cultivation and use of wheat differ in selective accuracy and repeatability coefficient.
Keywords: Triticum aestivum; quality control; experimental planning; repeatability; cultivar selection and recommendation